2022
DOI: 10.1002/er.8282
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and nitrous oxide from selective oxidation in a vanadium‐based catalytic diesel after‐treatment system

Abstract: Summary This study investigated the reduction of nitrogen oxides (NOx) and N2O emissions by selective catalytic oxidation (SCO) of an ammonia oxidation catalyst (AOC). This was conducted using a diesel engine with various oxidation catalysts, such as a diesel oxidation catalyst and a diesel particulate filter. The after‐treatment system was equipped with urea‐selective catalytic reduction (SCR) using a commercially available V2O5/TiO2 catalyst and an AOC to prevent ammonia slip. The performance of the system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…[14] Studies have shown that Cu-SSZ-13 exhibits greatly improved NO x conversion rates compared to iron and vanadiumbased catalysts. [15][16][17][18][19][20] However, it also poses a challenge in terms of secondary emission of N 2 O. [21][22][23][24][25] N 2 O, commonly known as "laughing gas", is considered a potent greenhouse gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Studies have shown that Cu-SSZ-13 exhibits greatly improved NO x conversion rates compared to iron and vanadiumbased catalysts. [15][16][17][18][19][20] However, it also poses a challenge in terms of secondary emission of N 2 O. [21][22][23][24][25] N 2 O, commonly known as "laughing gas", is considered a potent greenhouse gas.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Cu‐SSZ‐13 exhibits greatly improved NO x conversion rates compared to iron and vanadium‐based catalysts [15–20] . However, it also poses a challenge in terms of secondary emission of N 2 O [21–25] .…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect concerning the improvement in the nitrogen oxide reduction process is to find a more efficient catalyst that works over wider temperature ranges than the commonly used vanadium catalyst (V 2 O 5 -WO 3 -TiO 2 ) [20,21]. Recently, research into zeolite catalysts with deposited transition metal atoms has been of great interest to scientists [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%